2.5 years on: what are the effects of a 'frequent attenders' service in the Emergency Department?. (20th February 2019) - Sousa, Soraia; Hilder, Tracey; Burdess, Christopher; Bolton, Philippa
Abstract : This study focused on an evaluation over 2.5 years to establish if a frequent attenders' service in an Emergency Department (ED) impacted on the overall number of patients attending as well as the numbers of their attendances. For this, three patient lists from April-September 2015 and three lists from a matched period in 2017 were randomly selected and the two samples compared. Results showed both a reduction in the number of total patients identified as frequent attenders as well as a reduction on the number of attendances to ED. The study suggests that the implementation of a frequent attenders' service is associated with benefits, not only for the individual attendances per patient, but also in an overall reduction of the number patients classed as frequent attenders. Declaration of interest: The authors have no conflict of interest to declare regarding this manuscript.